Covid-19 vaccination acceptance among visitors of Erbil primary health care centers - Hawez Sulaiman , Karwan (Diyala Journal of Medicine, 2024)
Background: Vaccination is probably the most effective approach to prevent and control COVID-19. Studies assessing acceptance towards vaccination showed huge regional variations. Objective: To find out the rate of acceptance of Covid 19 vaccine and its associated factors as well as to explore out both the most frequent reasons behind acceptance or refusal of this vaccine and the most received and preferred type Patients and Methods: In this cross-sectional study, a convenience sample of 1000 visitors to primary health care centers (PHCCs) in Erbil/Iraq, aged 18 years and older, were collected from December 2021 to December 2022. A structured questionnaire was used for data collection through a direct interview. Results: The study showed that 43.9% of the participants accepted the vaccine. The main reason behind refusal (53.8%) was not trusting its development, while the main reasons for receiving were to protect themselves (44.2%), majority of those vaccinated (76.5%) received Pfizer, which was the most preferred type (67.4%), 10.3% of them were not completing the recommended dose and the most common reasons behind this were neglect and shortage of time (31%), and afraid from side effects (31%). A significant association found between vaccination practice with gender, education, occupation, family income and socioeconomic status. Vaccinated persons were less likely to be infected with COVID19 (20.7%) than nonvaccinated ones (62.7%). Conclusion: Less than half of the participants were accepted the vaccine and the acceptance rate significantly associated with male gender, education, occupation, family income, and socioeconomic status.